2018
DOI: 10.3791/57166
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Mesenchymal Stem Cells from Human Alveolar Periosteum and Effects of Vitamin D on Osteogenic Activity of Periosteum-derived Cells

Abstract: Mesenchymal stem cells (MSCs) are present in a variety of tissues and can be differentiated into numerous cell types, including osteoblasts. Among the dental sources of MSCs, the periosteum is an easily accessible tissue, which has been identified to contain MSCs in the cambium layer. However, this source has not yet been widely studied. Vitamin D3 and 1,25-(OH)2D3 have been demonstrated to stimulate in vitro differentiation of MSCs into osteoblasts. In addition, vitamin C facilitates collagen formation and bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…1L , M ). Periostea are niches for osteoprogenitor cells [ 34 , 35 ], which suggested that the new bone that gradually enveloped the graft particles might arise from this source. We therefore focused on how oral periosteum responded to tunneling and grafting procedures.…”
Section: Resultsmentioning
confidence: 99%
“…1L , M ). Periostea are niches for osteoprogenitor cells [ 34 , 35 ], which suggested that the new bone that gradually enveloped the graft particles might arise from this source. We therefore focused on how oral periosteum responded to tunneling and grafting procedures.…”
Section: Resultsmentioning
confidence: 99%
“…SGSCs express the markers CD24, CD29, CD34, CD44, CD49f, CD73, CD81, CD90, CD105, CD133, CD146, CD166, STRO-1, Nestin and aldehyde dehydrogenase (ALDH) (Table 4). There is a controversy if they express CD117 marker or not, as it was reported that SGSCs that were isolated from minor salivary glands do not express this marker [78,80,81]. These cells are capable of differentiate toward the classic MSCs lines; osteogenic, adipogenic and chondrogenic, and into amylase-expressing cells [82].…”
Section: Salivary Gland Stem Cellsmentioning
confidence: 99%
“…The surface of the bone is covered by the periosteum, which is a 50-150 μ m two-layer membrane with an abundance of nerves and blood vessels ( Figure 1 ). The outer fibrous layer is adjacent to the surrounding soft fibrous and muscular tissue, while the inner layer is highly vascularized and provides a niche for progenitor cells [ 26 , 27 ]. A large number of studies have already shown that precursor cells residing in the craniofacial bone periosteum play an important role in bone regeneration [ 28 ].…”
Section: Periosteummentioning
confidence: 99%
“…Therefore, to minimize potential damage, the use of appropriate ways to amplify and induce stem cells to differentiate toward the osteoblast lineage is particularly important. Wang et al reported that vitamin C and vitamin D were ideal stimulants of craniofacial PDLSCs for osteoblast differentiation in vitro [ 26 ]. Naung et al proposed a protocol to cultivate palate periosteum-derived MSCs in serum-free and xeno-free medium, which could become a useful source of MSCs for clinical applications [ 86 ].…”
Section: Application Of Craniofacial Stem Cellsmentioning
confidence: 99%